2021
DOI: 10.1186/s13014-021-01763-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning comparison of volumetric modulated arc therapy with the trilogy and the Halcyon for bilateral breast cancer

Abstract: Background The Halcyon is a new machine from the Varian company. The purpose of this study was to evaluate the dosimetry of the Halcyon in treatment of bilateral breast cancer with volumetric modulated arc therapy. Methods On CT images of 10 patients with bilateral breast cancer, four Halcyon plans with different setup fields were generated, and dosimetric comparisons using Bonferroni’s multiple comparisons test were conducted among the four plans.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The data presented here demonstrate the ability of the new Halcyon linac to produce robust and reliable treatment plans for hypofractionated prostate radiotherapy and confirm earlier investigations for different cancer types and radiotherapy regimes 16–21 . The patient‐specific QA showed no statistically significant differences in diode array‐based gamma pass rate measurements between Synergy and Halcyon.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The data presented here demonstrate the ability of the new Halcyon linac to produce robust and reliable treatment plans for hypofractionated prostate radiotherapy and confirm earlier investigations for different cancer types and radiotherapy regimes 16–21 . The patient‐specific QA showed no statistically significant differences in diode array‐based gamma pass rate measurements between Synergy and Halcyon.…”
Section: Discussionsupporting
confidence: 82%
“…The data presented here demonstrate the ability of the new Halcyon linac to produce robust and reliable treatment plans for hypofractionated prostate radiotherapy and confirm earlier investigations for different cancer types and radiotherapy regimes. 16 , 17 , 18 , 19 , 20 , 21 The patient‐specific QA showed no statistically significant differences in diode array‐based gamma pass rate measurements between Synergy and Halcyon. Agreement between the measured and calculated dose was high for both linear accelerators with a maximum deviation of 1.7% and 2.3% in ion chamber point dose for Synergy and Halcyon, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…This double‐staggered MLC has an effective leaf resolution of 5 mm. Several studies have compared the plan quality between a Halcyon and a TrueBeam, which comprises 40 central leaf pairs with a width of 5 mm and 20 peripheral leaf pairs with a width of 10 mm 9,10 . These studies have found that the Halcyon could provide a plan quality similar to that of the TrueBeam for VMAT techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have compared dosimetric differences between plans of breast cancer with those of Halcyon TM and other conventional linac. Sun et al compared the dosimetric difference between different arc plans with Halcyon TM and Trilogy, 20 with the prescription dose of 50 Gy per 25 fractions to the PTV. For the heart, Halcyon TM 4arc-plans reduced the V 30Gy value; however, D mean increased compared with Trilogy 8arc-plans (V 30Gy = 0.8% ± 0.5%, 1.8 ± 1.7%; D mean = 5.6 ± 0.6, 3.9 ± 1.1 Gy).…”
Section: Discussionmentioning
confidence: 99%